ANALISIS STRATEGI PENGELOLAAN WAKAF PRODUKTIF - Qolbi, Nurul; Ayuniyyah, Qurroh; Syauqi Beik, Irfan (Kasaba, 2022)
Islam, which once hegemoned world civilization, cannot be separated from its superior economic concept, one of which is about waqf. In Islamic history, the most famous waqf is the waqf of Umar bin Khattab and Uthman bin Affan, which is in the form of a palm garden and a well. These date palm gardens and wells can be called as productive waqf for the welfare of Muslims to this day. From this historical evidence, all Muslims should be aware that Islam already has a superior economic concept of the people, and has manifested in a civilization in the economic field long before the rise of the secular economy, which is precisely where Muslims today are oriented there. Baitul Wakaf is one of the productive waqf management institutions based in Jakarta. Based on the percentage of Baitul wakaf receipts in 2021, direct waqf contributed 82.5 percent and the surplus productive waqf only contributed 17.5 percent which identified the non-optimal management of productive waqf in Baitul wakaf. This study aims to find a priority strategy for productive waqf management in Baitul wakaf. The research method uses the analytical network process (ANP) method, which is a decision-making method with many interrelated criteria. The factors that influence the management of productive waqf in Baitul wakaf are divided into four aspects, they are strengths, weaknesses, opportunities and threats. The results of this study indicate that the most priority strategy in the management of productive waqf in the Baitul wakaf is to increase the professionalism of nazhir with a value of 0.2641, then followed sequentially by the strategy of education and socialization of waqf with a value of 0.25464, digitizing waqf services with a value of 0.24480 and followed by a strategy cooperation and partnership with internal and external institutions with the lowest score of 0.22492.